Intercultural Communication and ELT: A Classroom Experience - Jorge Turizo; Pablo Gómez (Asociación Colombiana de Profesores de Ingles, 2006)
The growing priority given to both cross-cultural awareness and interculturality in ELT requires EFL teachers to be aware of how culture arises out of language. However, the relation between language and culture seems hardly noticed and usually overlooked by EFL teachers. This paper discusses a) notions about how language and culture relate; b) a practical implementation of these notions through a reading and writing activity in an undergraduate EFL course at Universidad del Norte in Barranquilla; and c) implications for how language and culture can be incorporated into EFL courses.